Isolation, Selection and Identification of Polyaromatic Hydrocarbons (PAHs) Degrading Bacteria from Heavy Oil Waste (HOW)-Contaminated Soil - Yani, Mohamad; Charlena, Charlena; Mas?ud, Zainal Alim; Anas, Iswandi; Setiadi, Yadi; Syakti, Agung Dhamar (Bogor Agricultural University, Indonesia, 2020)
The heavy oil waste (HOW) containing polyaromatic hydrocarbon (PAHs) is a persistent organic pollutants (POPs) that difficult to degrade. The new PAH degrading consortium was investigated from HOW contaminated soil in North Sumatera of Indonesia. The isolation, selection and identification of polyaromatic hydrocarbon degrading bacteria from soil contaminated by HOW was conducted to solve a bioremediation process. The isolation microbes from soil contaminated by HOW was performed using a minimum ONR7a media and followed on marine agar media for purification purposes. From the performed isolation results, 11 isolates were able to degrade PAHs compounds, such as phenanthrene, dibenzothiophene, or fluorene compounds. They grew at pH range of 4.8-8.2 and performed on emulsification activity in paraffin from 0.150-0.662. Three of them showed the best performance on HOW biodegradation capability and then successfully selected and identified as Salipiger sp., Bacillus altitudinis, and Ochrobactrum anthropi. using 16S rDNA. The HOW biodegradation as TPH-degradation were 38.66%, 59.60%, and 47.16%, respectively. Those isolated bacteria could potentially be as bioremediation agents to develop on bioremediation process for soils contaminated by HOW.